Effects of Mindfulness-Based Stress Reduction on the Mental Health of Clinical Clerkship Students: A Cluster-Randomized Controlled Trial. (July 2017) - van Dijk, Inge; Lucassen, Peter L.B.J.; Akkermans, Reinier P.; van Engelen, Baziel G.M.; van Weel, Chris; Speckens, Anne E.M.
Abstract : Purpose: To examine the effect of mindfulness-based stress reduction training (MBSR) on the mental health of medical students during clinical clerkships. Method: Between February 2011 and May 2014, the authors conducted a cluster-randomized controlled trial of clerkships as usual (CAU) and clerkships with additional MBSR in medical students during their first year of clinical clerkships at a Dutch university medical center. MBSR consisted of eight weekly two-hour sessions, comprising didactic teaching, meditation exercises, and group dialogues. Students completed online assessments at baseline and after 3, 7, 12, 15, and 20 months. Outcome measures were psychological distress, positive mental health, life satisfaction, physician empathy, mindfulness skills, and dysfunctional cognitions as measured by validated tools. Results: Of 232 eligible students, 167 students (72%) participated and were randomized by clerkship group into MBSR (n = 83) or CAU (n = 84). The MBSR group reported a small reduction of psychological distress ( P = .03, Cohen's d = 0.20) and dysfunctional cognitions ( P = .05, Cohen's d = 0.18) and a moderate increase of positive mental health ( P = .002, Cohen's d = 0.44), life satisfaction ( P = .01, Cohen's d = 0.51), and mindfulness skills ( P = .05, Cohen's d = 0.35) compared with CAU during the 20-month follow-up. The authors detected no significant effect on physician empathy ( P = .18, Cohen's d = 0.27). Conclusions: MBSR appeared feasible and acceptable to medical clerkship students and resulted in a small to moderate improvement of mental health compared with CAU over the 20-month follow-up.